Strategies for Preventing and Managing Overweight and Obesity - Agbonlahor, Elvis I.; Ikhioya, Grace O.; Okaka, Richard O. (Pakistan Journal of Nutrition, 2009)
The purpose of this study was to reveal the various strategies for preventing and managing overweight and obesity in relation to reducing morbidity and mortality due to overweight and obesity. Thus, overweight and obesity are defined as Body Mass Index (BMI) of 25.0-29.9 kg/m2 and > 30.0 kg/m2 respectively. Overweight and obesity are complex multifactorial chronic diseases that develop from an interaction of genotype and the environment. It was therefore concluded that overweight and obesity involve the interaction of social, behavioural, cultural, physiological, metabolic and genetic factors. Thus, it was recommended that multi-component intervention which include nutrition and physical activities and strategies such as providing nutrition education or dietary prescription, physical activity, pharmacological and behavioural skills development and training could help to prevent and manage overweight and obesity.